A shield synchronous double-liquid grouting material and preparation method thereof

By using shield structure synchronous double-liquid grouting materials with components such as cement and fly ash, the problems of easy disintegration and high alkaline pollution in water are solved, and low alkaline and low shrinkage are achieved The grouting effect improves construction safety and material durability.

CN116768574BActive Publication Date: 2024-12-13BEIJING MUNICIPAL CONSTR +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310793681.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-13
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The existing cement-water glass double slurry is prone to disintegration in long-term soaking water, and the consolidation shrinkage rate is large, resulting in difficult surface settlement control and serious pollution of high alkaline substances.

Method used

Shield structure synchronous double-liquid grouting material including cement, fly ash, epoxy modified acrylic emulsion, aluminum sulfate, activated aluminum hydroxide, magnesium fluorosilicate, organic amine and nanosilicon sol, and through modification The acrylic emulsion forms an interpenetrating network structure, which improves the strength and water resistance of the solid body, and reduces alkalinity and shrinkage through organic amines and nanosilicon sols.

Benefits of technology

The grouting materials are achieved with low alkalinity, low shrinkage and environmentally friendly, which significantly reduces the ion dissolution of the solidified body in water, avoids disintegration and pollution, and improves construction safety and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116768574B_ABST
    Figure CN116768574B_ABST
Patent Text Reader

Abstract

The present invention provides a shield synchronous double liquid grouting material and a preparation method thereof, which belongs to the technical field of shield construction, and includes the following components by mass: 1-5 parts of component A, 0.5-5 parts of component B: wherein component A includes: 40-50 parts of cement, 10-20 parts of fly ash, 10-15 parts of epoxy-modified acrylic emulsion, and 40-50 parts of water; component B includes: 30-45 parts of early strength agent, 5-10 parts of active aluminum hydroxide, 3-15 parts of magnesium fluorosilicate, 2-8 parts of organic amine, 8-12 parts of nano silica sol, 10-20 parts of ammonium persulfate, and 0.5-1 parts of PH regulator. A shield synchronous double liquid grouting material and a preparation method thereof provided by the present invention have the characteristics of low price, excellent performance, small shrinkage, low alkali and environmental friendliness. It can solve the problems that the cement-water glass double liquid slurry consolidation body has a large shrinkage rate; it is easy to disintegrate, and the durability is poor; and the high alkaline material injected into the formation seriously pollutes the groundwater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of shield construction, and more specifically, relates to a shield synchronous double-liquid grouting material and a preparation method thereof. Background Art

[0002] Synchronous grouting is a form of grouting behind the segment and is a key process in the entire shield construction. The so-called synchronous grouting is to inject slurry behind the segment through the grouting pipe on the shield machine or the hoisting hole on the segment while the shield machine is excavating, filling the construction gap between the segment and the surrounding rock when the segment is separated from the shield tail, ensuring that the soil above the shield tunnel does not settle significantly and ensuring construction safety.

[0003] At present, the slurry commonly used in shield construction is cement-water glass double liquid slurry. This grouting material has a short gel time and can be accurately controlled within a few seconds to tens of minutes. The early strength increases quickly, so it is widely used. However, it also has some limitations: the diffusion radius of cement-water glass slurry is small, water glass is a highly alkaline substance, and injection into the stratum seriously pollutes the groundwater. The amount of water glass used is large, and quartz sand and other ores that can be used as silicon sources are mined in large quantities, resulting in resource scarcity and environmental damage. In addition, the cement-water glass consolidation body is immersed in water for a long time. Under the condition of contact with flowing water, a large amount of sodium ions will be dissolved, causing the consolidation body to pulverize, which in turn leads to a decrease in consolidation strength or even disintegration. The dissolved sodium ions will also pollute water resources. In addition, the shrinkage rate of the cement-water glass consolidation body is large, and the problem of surface settlement control needs to be solved. Summary of the invention

[0004] The purpose of the present invention is to provide a shield synchronous double-liquid grouting material and a preparation method thereof, aiming to replace water glass, reduce the pollution of high-alkaline substances to the stratum, and at the same time solve the technical problems of decreased consolidation strength, easy disintegration and large shrinkage rate of the consolidated body caused by long-term immersion of cement-water glass double-liquid slurry in water.

[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a shield synchronous double-liquid grouting material, comprising the following components in parts by mass:

[0006] 1-5 parts of component A, 0.5-5 parts of component B:

[0007] Component A includes: 40-50 parts of cement, 10-20 parts of fly ash, 10-15 parts of epoxy modified acrylic emulsion, and 40-50 parts of water;

[0008] Component B includes: 30-45 parts of aluminum sulfate, 5-10 parts of active aluminum hydroxide, 3-15 parts of magnesium fluorosilicate, 2-8 parts of organic amine, 8-12 parts of nano silica sol, 10-20 parts of ammonium persulfate, and 0.5-1 part of pH regulator.

[0009] Preferably, the organic amine is one or more of triethanolamine, N,N-dimethylethanolamine, and 1,4-butanediamine.

[0010] Preferably, the particle size of the nano-silica sol is 5-50 nanometers.

[0011] Preferably, the pH regulator is one or more of potassium citrate, lactic acid, tartaric acid, and phosphate.

[0012] Preferably, the particle size of the nano-silica sol is in the range of 5-30 nanometers.

[0013] Preferably, the early strength agent is aluminum sulfate.

[0014] Preferably, the following components are included in parts by weight:

[0015] 1 part of component A and 1 part of component B:

[0016] Component A includes: 50 parts of cement, 10 parts of fly ash, 15 parts of epoxy modified acrylic emulsion, and 40 parts of water;

[0017] Component B includes: 45 parts of early strength agent, 10 parts of active aluminum hydroxide, 10 parts of magnesium fluorosilicate, 5 parts of organic amine, 12 parts of nano silica sol, 20 parts of ammonium persulfate, and 1 part of pH regulator.

[0018] The present invention also provides a method for preparing a shield synchronous double-liquid grouting material, which is characterized by comprising the following steps:

[0019] Step 1, mix cement, fly ash, water and acrylic acid monomer, and stir evenly for 5-10 minutes to prepare component A;

[0020] Step 2, mixing and stirring the early strength agent, active aluminum hydroxide, magnesium fluorosilicate, organic amine, nano silica sol, anti-dispersant, ammonium persulfate, pH regulator and water for 5-10 minutes to obtain component B;

[0021] Step 3: Mix component A and component B in a 1:1 ratio by mass.

[0022] The beneficial effects of the shield synchronous double-liquid grouting material and the preparation method thereof provided by the present invention are as follows: compared with the prior art, the shield synchronous double-liquid grouting material and the preparation method thereof provided by the present invention have the characteristics of low price, excellent performance, small shrinkage, low alkali and environmental friendliness. It can solve the problems of large shrinkage rate of cement-water glass double-liquid slurry consolidation body; easy disintegration and poor durability; serious groundwater pollution caused by injection of high alkaline substances into the stratum and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 The figure shows a comparison of the states of the solidified body of the product of the present invention (Example 1) (left) and the solidified body of cement-water glass slurry (Example 4) (right) after immersion for 6 months under the same water-cement ratio. DETAILED DESCRIPTION

[0025] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0026] See also Figure 1 , now the shield synchronous double liquid grouting material provided by the present invention is described. The shield synchronous double liquid grouting material comprises the following components in mass fractions: 1-5 parts of component A and 0.5-5 parts of component B: wherein component A comprises: 40-50 parts of cement, 10-20 parts of fly ash, 10-15 parts of epoxy modified acrylic emulsion, and 40-50 parts of water; component B comprises: 30-45 parts of aluminum sulfate, 5-10 parts of active aluminum hydroxide, 3-15 parts of magnesium fluorosilicate, 2-8 parts of organic amine, 8-12 parts of nano silica sol, 10-20 parts of ammonium persulfate, and 0.5-1 part of pH regulator.

[0027] In the present invention, aluminum sulfate can quickly solidify cement and improve the setting and hardening rate of cement.

[0028] In the present invention, the use of active aluminum hydroxide can improve the fluidity of the slurry, enhance the strength of the slurry solid body, and enhance the acid corrosion resistance and sulfate corrosion resistance.

[0029] In the present invention, magnesium fluorosilicate can increase the tensile and flexural strength of cement and inhibit the fission and erosion of the slurry consolidation body.

[0030] In the present invention, the organic amine is one or more of triethanolamine, N,N-dimethylethanolamine, and 1,4-butanediamine. The use of organic amine has the following effects: 1. Accelerate the reaction rate and reduce the setting time of the material. Aluminum sulfate and organic amine can react with each other to generate aluminum ion complexes, which can react with cement quickly to make it set; 2. Improve the elasticity of the grouting material consolidation body to better adapt to and control surface settlement. Triethanolamine is preferably used as the organic amine.

[0031] In the present invention, the nano silica sol has fine particles, which have strong penetration power, can react with calcium hydroxide in the solid body to form calcium silicate, have strong bonding force, form a silicon film, and have excellent water resistance and water erosion resistance. The particle size of the nano silica sol is 5-50 nanometers. More specifically, the particle size of the nano silica sol is in the range of 5-30 nanometers.

[0032] In the present invention, the pH regulator is one or more of potassium citrate, lactic acid, tartaric acid, phosphate, hydrochloric acid, sulfuric acid, and acetic acid.

[0033] In the present invention, cement is one or more of silicate cement and sulphoaluminate cement.

[0034] In the present invention, the particle size of fly ash is 50-100 mm. The use of fly ash can improve the fluidity of slurry, and as one of the oligomers, it can improve the early strength and increase the strength of the consolidated body under the action of alkali excitation.

[0035] In the present invention, the epoxy-modified acrylic emulsion can form an interpenetrating network polymer structure to make the structure more compact; in addition, the epoxy-modified acrylic ester has strong adhesion, low shrinkage, and good chemical stability, and can effectively improve the surface settlement caused by the shrinkage of the consolidated body. The preparation method of the epoxy-modified acrylic emulsion can be: slowly drop an appropriate amount of benzoyl peroxide initiator into methyl methacrylate, heat to 70-85°C for reaction for 0.5-1h, then add quaternary ammonium salt and epoxy resin monomer to continue the reaction, drop deionized water at 60-80°C, and react at 90-120°C for 2-3h until it becomes an epoxy-modified acrylic emulsion. Under the action of the peroxide initiator benzoyl peroxide, the reaction activation energy is reduced, and the carboxyl active group on the acrylic ester copolymer is used to undergo a graft copolymerization reaction with the epoxy group of the low molecular weight E44 or E51 epoxy resin added later as a modifier to increase the compatibility between the two phases. The epoxy-modified acrylic emulsion can be obtained by purchase.

[0036] The present invention provides a shield synchronous double-liquid grouting material and a preparation method thereof, which, compared with the prior art, has the characteristics of low price, excellent performance, small shrinkage, low alkali, and environmental friendliness. It can solve the problems of large shrinkage rate of cement-water glass double-liquid slurry consolidation body; easy disintegration, poor durability; serious groundwater pollution caused by injection of high-alkaline substances into the stratum. This shield synchronous double-liquid grouting material is used to fill the construction gap between the pipe segment and the surrounding rock when the pipe segment is separated from the shield tail during tunnel shield construction, and plays a role of filling and reinforcement. This shield synchronous double-liquid grouting material can replace the double-liquid grouting material of alkaline water glass.

[0037] The following are examples and Figure 1 Further support and illustrate the technical solution of the present invention.

[0038] Example 1

[0039] A shield synchronous double-liquid grouting material, comprising the following components in parts by mass:

[0040] 1 part of component A and 1 part of component B:

[0041] Component A includes: 50 parts of cement, 10 parts of fly ash, 15 parts of epoxy-modified acrylic emulsion, and 40 parts of water; the specific type of cement is PO42.5.

[0042] Component B includes: 45 parts of aluminum sulfate, 10 parts of active aluminum hydroxide, 10 parts of magnesium fluorosilicate, 5 parts of triethanolamine, 12 parts of nano silica sol, 20 parts of ammonium persulfate, and 1 part of pH regulator.

[0043] The pH regulator is one or more of hydrochloric acid, sulfuric acid, and acetic acid.

[0044] Example 2

[0045] A shield synchronous double-liquid grouting material, comprising the following components in parts by mass:

[0046] 1 part of component A and 1 part of component B:

[0047] Component A includes: 45 parts of cement, 15 parts of fly ash, 15 parts of epoxy modified acrylic emulsion, and 50 parts of water; the specific type of cement is PO42.5

[0048] Component B includes: 40 parts of aluminum sulfate, 10 parts of active aluminum hydroxide, 15 parts of magnesium fluorosilicate, 2 parts of triethanolamine, 8 parts of nano silica sol, 10 parts of ammonium persulfate, and 0.8 parts of pH regulator.

[0049] The pH regulator is one or more of hydrochloric acid, sulfuric acid, and acetic acid.

[0050] Example 3

[0051] A shield synchronous double-liquid grouting material, comprising the following components in parts by mass:

[0052] 1 part of component A and 1 part of component B:

[0053] Component A includes: 40 parts of cement, 20 parts of fly ash, 10 parts of epoxy modified acrylic emulsion, and 50 parts of water;

[0054] Component B includes: 35 parts of aluminum sulfate, 10 parts of active aluminum hydroxide, 10 parts of magnesium fluorosilicate, 6 parts of triethanolamine, 10 parts of nano silica sol, 15 parts of ammonium persulfate, and 0.5 parts of pH regulator.

[0055] Example 4 (Comparative Example)

[0056] Component A: 50 parts cement, 40 parts water;

[0057] Component B, 20 parts of water glass (water glass is selected from Jinan Xinyi Chemical Co., Ltd., Baume degree 40-42°).

[0058] sample Initial setting time (min) TDS(7d) Shrinkage rate (%) PH(1d) Example 1 3 6871ppm 3% 8 Example 2 5 7025ppm 6% 9 Example 3 6 7635ppm 9% 8 Example 4 (Comparative Example) 1 31150ppm 20% 14

[0059] Table 1

[0060] TDS: Total dissolved solids, mainly refers to the total amount of all soluble metal cations and acid-base anions in water.

[0061] It can be concluded from Table 1 that compared with the cement-water glass slurry consolidation body of Example 4, the dissolved solid (TDS) content after soaking in water for 7 days is 31150ppm (31150mg / L), and the dissolved solid (TDS) content of Examples 1-3 after soaking in water for 7 days is 6871-7635ppm, which is greatly reduced compared with the cement-water glass slurry consolidation body, which means that the ion dissolution amount of the consolidation body is greatly reduced, avoiding the strength reduction and disintegration phenomenon after the consolidation body is soaked in water. And the pH value of the cement-water glass slurry consolidation body of Example 4 after soaking in water for 1 day is 14 (high alkalinity), and the pH value of Examples 1-3 after soaking in water for 1 day is 8-9 (low alkalinity), which means that compared with the cement-water glass consolidation body, the slurry consolidation body of the present invention has less water pollution after soaking in water.

[0062] In addition, under natural drying conditions, by comparing the 28d shrinkage rates of the cement-water glass consolidation body (Example 4) and the product examples 1-3 of the present invention, it can be seen that the natural drying shrinkage rate of the product of the present invention is much smaller than the natural drying shrinkage rate of cement-water glass, which can reduce the problem of controlling surface settlement caused by the shrinkage of the consolidation body in the later stage.

[0063] The present invention also provides a method for preparing a shield synchronous double-liquid grouting material, which is characterized by comprising the following steps:

[0064] Step 1, weigh each raw material according to the preset component formula ratio, then mix cement, fly ash, water, and acrylic acid monomer, and stir evenly for 5-10 minutes to obtain component A;

[0065] Step 2, mixing and stirring the early strength agent, active aluminum hydroxide, magnesium fluorosilicate, organic amine, nano silica sol, anti-dispersant, ammonium persulfate, pH regulator and water for 5-10 minutes to obtain component B;

[0066] Step 3: Mix component A and component B in a 1:1 ratio by mass.

[0067] It should be noted that all the raw materials used above can be obtained by purchasing. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing shield synchronous double-liquid grouting material, characterized in that: A shield synchronous double-liquid grouting material, comprising the following components in parts by mass: 1 part of component A and 1 part of component B: Component A includes: 50 parts of cement, 10 parts of fly ash, 15 parts of epoxy modified acrylic emulsion, and 40 parts of water; Component B includes: 45 parts of early strength agent, 10 parts of active aluminum hydroxide, 10 parts of magnesium fluorosilicate, 5 parts of organic amine, 12 parts of nano silica sol, 20 parts of ammonium persulfate, and 1 part of pH regulator; The organic amine is one or more of triethanolamine, N,N-dimethylethanolamine, and 1,4-butanediamine; the pH regulator is one or more of potassium citrate, lactic acid, tartaric acid, and phosphate; the particle size of the nano-silica sol is in the range of 5-30 nanometers; the early strength agent is aluminum sulfate; The preparation method comprises the following steps: Step 1, mix cement, fly ash, water and epoxy modified acrylic emulsion, stir evenly for 5-10 minutes to prepare component A; Step 2, mixing and stirring the early strength agent, active aluminum hydroxide, magnesium fluorosilicate, organic amine, nano silica sol, anti-dispersant, ammonium persulfate, pH regulator and water for 5-10 minutes to obtain component B; Step 3: Mix component A and component B in a 1:1 ratio by mass.

Citation Information

Cited By

  • TBM synchronous grouting material and construction method

    CN120081623A